Socio-political attitudes 1979 - Ekehammar, Bo (Stockholm University, 2026)
The aim of the study is basically the same as in Socio-Political Attitudes 1975. The central aim of the study is to investigate various aspects of political perception as a function of socio-political ideology. The politically perceived objects consist mainly of political parties, party leaders, and countries. Political perception is measured using multidimensional scaling, semantic differential, and political differential techniques. Political ideology is operationalized through party affiliation and socio-political attitudes (measured using a specially designed scale). Based on these data, certain individual-level indices of cognitive articulation and cognitive differentiation are generated and subsequently related to the individual’s socio-political ideology.

In the first part of the study, several new questions concerning politics within the family and in the media have been added. Questions regarding cars, housing conditions, and siblings have also been included. The assessments of religiosity and extremism have been removed.
The second part deals with the same group. Evaluations of the Swedish political parties and party leaders are included in this section together with party preferences.

Please note that the data files are in .ORIG format and require some conversion before use.

Syftet med undersökningen är i huvudsak detsamma som i Socio-Political Attitudes 1975. Det centrala syftet med studien är att undersöka olika aspekter av politisk perception som en funktion av sociopolitisk ideologi. De politiskt uppfattade objekten består huvudsakligen av politiska partier, partiledare och länder. Mätningen av politisk perception görs genom multidimensionell skalning, semantisk differential och politisk differential. Politisk ideologi operationaliseras genom partitillhörighet och sociopolitiska attityder (mätta med en särskilt utformad skala). Utifrån dessa data genereras vissa index på individnivå för kognitiv artikulation och kognitiv differentiering, vilka sedan relateras till individens sociopolitiska ideologi.

I den första delen av undersökningen finns några nya frågor om politik i familjen och i medierna. Frågor om bilar, boendeförhållanden och syskon har också lagts till. Bedömningarna av religiositet och extremism har tagits bort.
Den andra delen behandlar samma grupp. Bedömningar av de svenska politiska partierna och partiledarna återfinns i denna del tillsammans med partisympatierna.

Observera att datafilerna är i .ORIG-format och kräver viss konvertering före användning.
Sociopolitiska attityder 1979
Keywords: Political behaviour and attitudes; Politiska beteenden och attityder; Youth; Ungdomar; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap